(untitled) (Journal of Parents and Teachers, 2018)
The vast majority of educational projects fall into the same mistakes. The mediation projects try to start without the basic logistical knowledge to achieve the effectiveness and sustainability of the project. Pon Solution advises dozens of educational centers for the creation of mediation teams, intervening in turn in educational, family and business conflicts. 6 keys to review the project that is being applied in the center. 6 keys to anticipate events.